Design and Build Reminder for Arduino Based Drug Schedule Consumption System - Moch Faizal Deva Prayogo; Wahyu Sapto Aji (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
The medication reminder system is designed to set the patient's daily drug consumption schedule. This system uses RTC DS1302 as a time saver and as an alarm, while the output is in the form of a buzzer and LED. The Schedule of drug consumption can be arranged morning, afternoon, and evening according to patient needs. On the device, there is a DVD motor drive that is used to extract the drug automatically. There is also a temperature sensor in the form of DHT11 to monitor the temperature of the device so that the quality of the drug is maintained. The system was tested using 3 drug slots in it. The device is set using a keypad to make it easier for patients to manage medication consumption schedules. After being tested, the results of the alarm output sound in the form of a buzzer. and the output of a medicine container that uses a DVD motor automatically. After the device is tested, an alarm in accordance with what is set schedule indicates the tool is running in accordance with the destination.